A Bánság és a Balkán gazdasági kapcsolatrendszere a XX. század elején - Kókai, Sándor (Közép-Európai Közlemények, 2014)
This paper tries to answer the question whether the Bánság (Banat), often referred to as the gate of the Balkans, which is a special historical, political, economic and geographical region, was able to meet the geostrategic and economic challenge occurring at the end of the Age of Dualism to become an economic link between the Balkans and the Austro–Hungarian Empire. During the examination of economic linkages it has been revealed that the region was not able to meet this challenge, as a result the Bánság (Banat) became neither the gate of the Eastern Balkans nor the Central Balkans, which means that goods transported within the framework of the international division of labour did not flow across the Bánság. The transport of the Szeged–Timisoara–Orsova railroad and the Lower-Danube waterway did not have any impact on the region, also it was not able to profit from transit trade, which among other things can be due to the fact that economic geographic structures and their connection points in the Balkans developed too late and they did not have integral linkages. The autonomy of the Banatian Military Frontier until 1876 impeded this problem further.